Women leadership and community development - Hassan, Zaharah; Silong, Abu Daud (EuroJournals, 2008)
Traditionally, community affairs and administration has been the domain of men. This is evident from the gender imbalance of leaders and office bearers across community, local council and associations. Women have not been active in local politics and are relatively inactive in public processes due to institutional, socio-economic and cultural constraints. However, times are changing. There is now an acceptance that women can and do play a vital role in community affairs, particularly in contributing to the achievement of community security, development and progress. This article documents the experiences of three female leaders in their quest to unite and lead their peers in the betterment of their communities. This qualitative research employed various methodologies such as in-depth interviews, observations and document analysis. Specifically, the research findings described and analyzed the leadership understanding and styles, reasons for becoming leaders, barriers of women leadership and strategies employed by these women leaders in developing the community.